New therapeutic perspectives in CCDC6 deficient lung cancer cells. Issue 9 (24th October 2014) - Morra, Francesco; Luise, Chiara; Visconti, Roberta; Staibano, Stefania; Merolla, Francesco; Ilardi, Gennaro; Guggino, Gianluca; Paladino, Simona; Sarnataro, Daniela; Franco, Renato; Monaco, Roberto; Zitomarino, Federica; et al.
<x xml:space="preserve">Abstract</x> Non‐small cell lung cancer (NSCLC) is the main cause of cancer‐related death worldwide and new therapeutic strategies are urgently needed. In this study, we have characterized a panel of NSC lung cancer cell lines for the expression of coiled‐coil‐domain containing 6 (CCDC6), a tumor suppressor gene involved in apoptosis and DNA damage response. We show that low CCDC6 protein levels are associated with a weak response to DNA damage and a low number of Rad51 positive foci. Moreover, CCDC6 deficient lung cancer cells show defects in DNA repair via homologous recombination. In accordance with its role in the DNA damage response, CCDC6 attenuation confers resistance to cisplatinum, the current treatment of choice for NSCLC, but sensitizes the cells to olaparib, a small molecule inhibitor of the repair enzymes PARP1/2. Remarkably, the combination of the two drugs is more effective than each agent individually, as demonstrated by a combination index <1. Finally, CCDC6 is expressed at low levels in about 30% of the NSCL tumors we analyzed by TMA immunostaining. The weak CCDC6 protein staining is significatively correlated with the presence of lymph node metastasis (p ≤ 0.02) and negatively correlated to the disease free survival (p ≤ 0.01) and the overall survival (p ≤ 0.05). Collectively, the data indicate that CCDC6 levels provide valuable insight for OS. CCDC6 could represent a predictive biomarker of resistance to conventional single mode therapy and yield insight on tumor sensitivity to PARP inhibitors in NSCLC.